Questionnaire survey as a mechanism to monitor the satisfaction of investors - Utegenova, А.М. (BUKETOV BUSINESS REVIEW, 2017)
The article discusses the criteria of investment attractiveness of the country. A study conducted to identify the needs of foreign and private investors. As a result of the survey the main problems of investment identified. The analysis of the investment climate in the Republic of Kazakhstan carried out. In this research paper the current situation is analyzed, mechanisms to improve the investment climate and reduce corruption are proposed. The studies of World Bank Group authoritative international expert organizations, as well as the ratings of "Doing Business" are considered. Global trends in investment policies are examined, foreign direct investment are analyzed. To improve the investment environment in the Republic of Kazakhstan fundamental directions in addressing existing challenges and problems are marked on the basis of the generalized international experience and on the basis of the conducted research, the recommendations of authoritative international expert centers. In this article a high urgency of the problems of counteraction to corruption offenses is underlined. The analysis of some regulatory legal acts of the Republic of Kazakhstan that contain anticorruption norms, and on state support for direct investment is undertaken. The study developed recommendations for improving the investment climate and reduce the level of corruption in the Republic of Kazakhstan.